2006
DOI: 10.1103/physreva.73.032102
|View full text |Cite
|
Sign up to set email alerts
|

Hardy’s criterion of nonlocality for mixed states

Abstract: We generalize Hardy's proof of nonlocality to the case of bipartite mixed statistical operators, and we exhibit a necessary condition which has to be satisfied by any given mixed state σ in order that a local and realistic hidden variable model exists which accounts for the quantum mechanical predictions implied by σ. Failure of this condition will imply both the impossibility of any local explanation of certain joint probability distributions in terms of hidden variables and the nonseparability of the conside… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(35 citation statements)
references
References 19 publications
0
35
0
Order By: Relevance
“…The sets in question are sets of values of hidden variables which imply certain outcomes of measurements. Following the steps in [26], only slightly generalized to different ǫ ν and equalities instead of bounds for the joint probabilities, we immediately find the necessary condition…”
Section: Test But What Is the Precise Relationship Between Hardy's Tmentioning
confidence: 94%
See 4 more Smart Citations
“…The sets in question are sets of values of hidden variables which imply certain outcomes of measurements. Following the steps in [26], only slightly generalized to different ǫ ν and equalities instead of bounds for the joint probabilities, we immediately find the necessary condition…”
Section: Test But What Is the Precise Relationship Between Hardy's Tmentioning
confidence: 94%
“…Hardy managed to construct a pure state for which, according to QM, just this happens [17]. Later, his argument was generalized and it was shown that almost any pure state of any system with an arbitrary number of particles and arbitrary dimension of Hilbert space can be used [30,31,32], and even a large class of mixed states [26].…”
Section: B Ideal Hardy's Testmentioning
confidence: 99%
See 3 more Smart Citations